2021
DOI: 10.1088/1755-1315/882/1/012066
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of carbon active processed from coal in treating the acid mine drainage at a laboratory scale

Abstract: Low to medium calorie coal reserves dominate Indonesia area. Referring to such amount, the potential for coal synthesis into activated carbon is also massive. The potential utilization of activated carbon from coal to process the acid mine drainage is still developing. This research aims to see the effect of activated carbon to the acid mine drainage from coal mining in a laboratory scale using a weight basis and the contact time between activated carbon and acid mine drainage. The sample is taken from one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
1
1
1
Order By: Relevance
“…The result of this study's Mn(II) adsorption (99.9%) was greater than that of earlier research, which reported Mn(II) absorption of 26.3% (Suliestyah et al, 2021a), 56% (Suliestyah et al, 2020b) and 92.89% (Sitorus, 2015), respectively. This study showed that the activated carbon made from coal with H3PO4 activation has a high adsorption capacity for Fe(II) and Mn(II) metals in artificial AMD waste, thus having a potency to be used as an adsorbent in AMD treatment.…”
Section: Contact Time Of Adsorption (Minutes)contrasting
confidence: 88%
See 1 more Smart Citation
“…The result of this study's Mn(II) adsorption (99.9%) was greater than that of earlier research, which reported Mn(II) absorption of 26.3% (Suliestyah et al, 2021a), 56% (Suliestyah et al, 2020b) and 92.89% (Sitorus, 2015), respectively. This study showed that the activated carbon made from coal with H3PO4 activation has a high adsorption capacity for Fe(II) and Mn(II) metals in artificial AMD waste, thus having a potency to be used as an adsorbent in AMD treatment.…”
Section: Contact Time Of Adsorption (Minutes)contrasting
confidence: 88%
“…The carbon itself has been activated using ZnCl2, and its application in liquid waste can adsorb Fe(II) metal by 96% (Suliestyah et al, 2020a). The adsorption of coalactivated carbon with ZnCl2 activation on Fe(II) and Mn(II) metals in AMD has been carried out, which resulted in the adsorption of 99.7-100% Fe(II) and 26.5-56 Mn(II)% (Suliestyah et al, 2020b), (Suliestyah et al, 2021a). The results showed that coal-activated carbon has a high adsorption capacity for Fe(II) metal but is still low for Mn(II) metal.…”
Section: Introductionmentioning
confidence: 99%
“…Yakni absorbat yang terakumulasi pada permukaan adsorben akan semakin banyak. Dengan demikian, ketika proses adsorpsi berlangsung pada kondisi yang optimum maka akan diperoleh karbon aktif dengan kapasitas adsorpsi yang optimum (Suliestyah et al, 2021). Berdasarkan data hasil pengolahan model isotherm Freundlich untuk logam Fe pada tabel 4 maka dapat dibuat kurva hubungan log Qe dan log Ce yang dapat dilihat pada gambar 3.…”
Section: Penentuan Model Isotermal Adsorpsiunclassified